Strategi Pengembangan Usaha Garam di Desa Antiga Kelod, Kecamatan Manggis, Kabupaten Karangasem (Jurnal Agribisnis dan Agrowisata, 2026)
Salt Business Development Strategy in Antiga Kelod Village, Manggis District, Karangasem Regency. The potential for production and demand for salt is increasing along with industrial development and increasing population. Salt business in Antiga Kelod Village, it is necessary to develop a strategy that aims to identify internal and external factors for the development of the salt business in Antiga Kelod Village. then formulate general strategies, alternative strategies, strategies priorities and appropriate program development strategies to be implemented in the salt business in Antiga Kelod Village. This study uses qualitative and quantitative research methods. The strategy formulation process is carried out through an analysis of the IE matrix, the SWOT matrix and the QSPM matrix. Based on the results of internal factor analysis, the main strength of the salt business in Antiga Kelod Village is the attractive product characteristics (0,32). The main weakness is the low interest of farmers in the recording and marketing of cooperatives that have not been effective (0,14). The external factor that becomes the main opportunity is the government's role in overcoming the problem of salt (0,40). The main threat is the presence of local salt competitors from other regions (0,22). Based on the results of the SWOT matrix analysis, there are nine alternative strategies.
Keywords: Antiga Kelod Salt; internal and external factors; development strategy